Parental acceptance of the utilization of silver diamine fluoride on their child’s primary and permanent teeth - Bagher, Sara M (Patient Prefer Adherence, 2019)
Purpose: Silver diamine fluoride (SDF) is an effective caries control agent. The aim of our study was to investigate the parental acceptance of the utilization of SDF on their child’s primary and permanent teeth and to determine the factors that influence their decision-making. Patients and methods: This descriptive cross-sectional study included parents of healthy children aged 12 years and younger and currently receiving dental treatment. The interview questionnaire was conducted and pre-tested for face and content validity. The trained interviewing dentists showed colored pictures of primary and permanent teeth before and after receiving SDF treatment. The statistical significance was set at P<0.05. Results: A total of 104 parents were included in the study. The mean parental rating of treatment acceptability of the staining associated with SDF was 3.9±1.95. The plurality considered the staining caused by SDF treatment strongly not acceptable 46 (43.4%). Parental acceptance of SDF treatment was significantly affected by the location and type of teeth. Parents showed significantly higher acceptance of SDF treatment on their child’s primary compared to permanent teeth and posterior compared to anterior in both dentitions (P<0.001). In addition, parents of children with a history of uncooperative behavior during previous dental treatment were significantly more accepting of SDF treatment regardless of the type and location of the teeth. Conclusion: Parental acceptance of SDF increased for primary compared to permanent teeth, on anterior compared to posterior teeth in both dentitions and for uncooperative children.